Pelanggaran, ketidakpercayaan, dan kecerobohan: Koninklijk Bataviaasch Genootschap van Kunsten en Wetenschappen di Pameran Kolonial Internasional Paris, 1931 - Efendi, Muhammad Yusuf (Historiography: Journal of Indonesian History and Education, 2024)
Abstract This research discusses the participation of the Royal Batavia Society of Arts and Sciences (KBG) in the 1931 International Colonial Exhibition. The KBG was a cultural institution founded in Batavia in 1778. As a colonial cultural institution, KBG participated in the exhibition as part of the representation of the Dutch East Indies. This research is important because previous studies have not described in depth the process of KBG's involvement in the exhibition. The research uses the historical method, including topic selection, source collection, verification, interpretation, and historiography. The primary sources used are the archives of the Koninklijk Bataviaasch Genootschap van Kunsten en Wetenschappen, the annual report of the KBG’s and the Pieter Adriaan Jacobus Moojen archive. The results showed that the KBG management had violated the institution's principles by lending out its museum collection. They did not fully trust the exhibition committee so they handed over the responsibility of managing the collection to another party. The conditions proposed by the Museum Council were also not all met. As a result, the entire KBG collection that was sent fell victim to the fierce fire when it burned down the Dutch Pavilion. To prevent this from happening again, the board then amended the institution's statutes. Abstrak Penelitian ini membahas tentang partisipasi Koninklijk Bataviaasch Genootschap van Kunsten en Wetenschappen (KBG) dalam Pameran Kolonial Internasional tahun 1931. KBG merupakan lembaga kebudayaan yang didirikan di Batavia pada tahun 1778. Sebagai sebuah lembaga kebudayaan kolonial, KBG turut serta menjadi peserta pameran sebagai bagian dari representasi Hindia Belanda. Penelitian ini penting dilakukan karena studi-studi sebelumnya belum menguraikan secara mendalam mengenai proses keterlibatan KBG dalam pameran tersebut. Penelitian menggunakan metode sejarah dengan lima tahapan, yaitu pemilihan topik, pengumpulan sumber, verifikasi, interpretasi, dan historiografi. Sumber primer yang digunakan adalah arsip Koninklijk Bataviaasch Genootschap van Kunsten en Wetenschappen, laporan tahunan KBG, dan arsip Pieter Adriaan Jacobus Moojen. Hasil penelitian menunjukkan bahwa pengurus KBG telah melanggar prinsip lembaga dengan meminjamkan koleksi museumnya. Mereka tidak sepenuhnya percaya dengan panitia pameran sehingga menyerahkan tanggung jawab pengelolaan koleksi ke pihak lain. Syarat yang diajukan Dewan Museum juga tidak semuanya dipenuhi. Akibatnya, seluruh koleksi KBG yang dikirim menjadi korban ganasnya api ketika membakar Paviliun Belanda. Agar tidak terulang kembali, pengurus kemudian mengamandemen statuta lembaga.